Pengaruh Budaya Kerja, Semangat Kerja dan Kinerja Karyawan terhadap Kepuasan Kerja Karyawan PT RJN - Wisnu Andika Dio Putra; Indah Yuni Astuti; Iing Sri Hardiningrum (Jurnal Bisnis Kreatif dan Inovatif, 2025)
Companies face a variety of human resources with varying characteristics and abilities, which significantly impact employee performance. The influence of work culture, work morale, and employee performance, including variables such as discipline, mutual respect, individual passion, team spirit, quality, punctuality, workers, salary, promotions, supervision, and coworkers, is crucial in determining how significantly they influence employee job satisfaction at PT RJN. By understanding this relationship, the director or leader of PT RJN can predict employee responses to job satisfaction, maintain it, and improve it so employees feel more comfortable and at ease in their work. The sampling technique in this study used a saturated sampling method, a non-probability sampling method. This research employed a quantitative approach with a concrete data processing methodology. The population consisted of 40 employees in the production, administration, marketing, and distribution departments. The sample used in this study was derived from primary data obtained from 40 respondents from the production department who were still actively working at PT RJN. Data were obtained through questionnaires and observations. From the results of the analysis that has been done, based on the results of partial testing, the job satisfaction of PT RJN employees is positively and significantly influenced by the variables of work culture, work spirit, and employee performance. Based on the results of simultaneous testing, the job satisfaction of PT RJN employees is significantly influenced by the variables of work culture, work spirit, and performance characteristics. significantly influence employee job satisfaction. This is known from the correlation analysis as follows: r value = 0.377 or 37.7% and then the remaining 62.3% comes from various factors outside this concentration and is influenced by other variables not examined in this study.